Foundations of practical ethics. (October 2016) - Hain, Richard; Saad, Toni
Abstract: Principlism remains the dominant framework for addressing ethical quandaries in medical practice. It sets out four principles clinicians should consider that require specification to a particular set of circumstances. There is no hierarchy among the principles; any special prominence given to respect for autonomy is a cultural accretion that is not claimed by the authors of principlism. Principlism does not set out a single consistent or coherent moral theory. Instead, it summarizes for the clinician's convenience the relevant reasoning of more fundamental theories, including those in which the emphasis is on a doctor's intentions (deontological theories), those focussing on the outcome of doctors' actions (consequentialist theories) and those relying on the nature and disposition of the doctor herself (virtue ethics). As sources of guidance in making complex moral decisions in clinical practice, each of these has its attractions and limitations. Principlism does not represent an alternative analytical mechanism, nor is it an exhaustive exposition of those theories. Its strength is that it provides a summary of some of their most important reasoning, in a way that is clear, easy to assimilate and easy to recall at the moment when clinical decisions need to be made in practice.